Pyoderma gangrenosum of the breast 17 years after breast cancer treatment. Issue 3 (18th March 2020) - Pellegrino, Samantha Ann; Cham, Alvin; Pitcher, Meron
Abstract : We present a case of pyoderma gangrenosum (PG) affecting the breast of a 74-year-old woman, with a history of breast cancer treated with breast conserving surgery and adjuvant radiotherapy 17 years prior. She presented to the hospital with worsening breast ulceration, after a punch biopsy was performed at the site. She had surrounding cellulitis and concurrent infection to that breast which required antibiotics. The ulceration persisted even after treatment, and incisional biopsies of the area of ulceration confirmed the diagnosis of PG. Her condition was managed effectively with the use of immunosuppressive therapy, and she continued to display a good clinical response 2 months post discharge from the hospital.